2017
DOI: 10.2147/copd.s132825
|View full text |Cite
|
Sign up to set email alerts
|

The direct and indirect costs of managing chronic obstructive pulmonary disease in Greece

Abstract: ObjectiveCOPD is associated with significant economic burden. The objective of this study was to explore the direct and indirect costs associated with COPD and identify the key cost drivers of disease management in Greece.MethodsA Delphi panel of Greek pulmonologists was conducted, which aimed at eliciting local COPD treatment patterns and resource use. Resource use was translated into costs using official health insurance tariffs and Diagnosis-Related Groups (DRGs). In addition, absenteeism and caregiver’s co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 12 publications
2
35
0
Order By: Relevance
“…There was a considerable impact of COPD on productivity loss in the working-age population, which was evident from the costs incurred due to productivity loss. Indirect costs associated with COPD are significant; in the US, the indirect costs for COPD patients accounted for 27%–61% of the total medical costs, depending on the population studied, while in Greece, it accounted for 37.5% of the annual medical cost for COPD patients 38,39. Although the indirect costs were estimated considering only the productivity loss, the number of patients retiring due to COPD highlights a considerable economic impact of the disease in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…There was a considerable impact of COPD on productivity loss in the working-age population, which was evident from the costs incurred due to productivity loss. Indirect costs associated with COPD are significant; in the US, the indirect costs for COPD patients accounted for 27%–61% of the total medical costs, depending on the population studied, while in Greece, it accounted for 37.5% of the annual medical cost for COPD patients 38,39. Although the indirect costs were estimated considering only the productivity loss, the number of patients retiring due to COPD highlights a considerable economic impact of the disease in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…Combination therapies, as well as the cost of comorbidity-associated management, are the reasons for the large increase in medication expense in this group of patients [106,107]. Another study estimated the annual per-patient direct costs (including the cost of exacerbations, hospitalisation and pharmaceutical treatment) of COPD to be €2810, 54% of which reflected the management of exacerbations [109]. When indirect (work loss days per year and other productivity losses) and patient time costs were added to direct costs, the total annual burden of COPD in Greece rose sharply to €4730 per patient [109].…”
Section: Economic Burden Of Copd Exacerbations During the Greek Crisismentioning
confidence: 99%
“…In Greece, the only study to have made an estimate of the total cost of COPD is the one of Souliotis et al, 15 which reports that the total cost of COPD in Greece is €4,729.9, of which €2,809.70 was for direct medical costs (€835 for maintenance phase costs and €462.30 for additional resources cost [such as LTOT] while €1,512.40 was for exacerbations costs). However, due to the fact that in this study a different methodology was used (the study was based on expert opinion rather than patient-level data) and different parameters were taken into consideration, it is difficult to compare with the current study.…”
Section: Discussionmentioning
confidence: 99%
“…14 In Greece, there are very few studies – using different methods – estimating the cost of COPD. A recent study reported a total annual per-patient cost of €4,730, 15 while another study focusing on severe exacerbations reported a cost of €1,711 per severe exacerbation. 16 …”
Section: Introductionmentioning
confidence: 99%